ChemInform Abstract: Gold(I)‐Catalyzed Synthesis of Tetrahydrocarbazoles via Cascade [3, 3]‐Propargylic Rearrangement/[4 + 2] Cycloaddition of Vinylindoles and Propargylic Esters. Issue 24 (27th May 2016) - Pirovano, Valentina; Arpini, Elisa; Dell'Acqua, Monica; Vicente, Ruben; Abbiati, Giorgio; Rossi, Elisabetta
Abstract: Highly substituted tetrahydrocarbazole derivatives are obtained in high yields and diastereoselectivities.